Evidence for a large-magnitude Holocene eruption of Mount Rittmann (Antarctica): A volcanological reconstruction using the marine tephra record. (15th December 2020) - Di Roberto, A.; Albert, P.G.; Colizza, E.; Del Carlo, P.; Di Vincenzo, G.; Gallerani, A.; Giglio, F.; Kuhn, G.; Macrì, P.; Manning, C.J.; Melis, R.; Miserocchi, S.; et al.
Abstract: In Antarctica, the near-source exposures of volcanic eruption deposits are often limited as they are not well preserved in the dynamic glacial environment, thus making volcanological reconstructions of explosive eruptions extremely challenging. Fortunately, pyroclastic deposits from explosive eruptions are preserved in Southern Ocean sediments surrounding Antarctica, and the tephrostratigraphy of these sequences offers crucial volcanological information including the timing and tempo of past eruptions, their magnitude, and eruption dynamics. Here we report the results of a tephrostratigraphy and tephrochronology study focused on four sediment cores recovered from the Wood Bay area in the western Ross Sea, Antarctica. In all these sedimentary sequences, we found a well-stratified primary tephra of considerable thickness, up to 80 cm, hereafter named the Aviator Tephra (AVT). According to the characteristics of the tephra deposit and its distribution, the AVT was associated with an eruption of considerable intensity, potentially representing one of the largest Holocene eruptions recorded in Antarctica. Based on the major and trace element geochemistry and the mineral assemblage of the tephra, Mount Rittmann was identified as the source of the AVT. A Holocene age of ∼11 ka was determined by radiocarbon dating organic material within the sediments and 40 Ar- 39 Ar dating of alkali-feldspar crystals included in the tephra. Eruption dynamics were initially dominated by hydromagmatic magma fragmentation conditions producing a sustained, relatively wet and ash-rich eruptive cloud. The eruption then evolved into a highly energetic, relatively dry magmatic Plinian eruption. The last phase was characterized by renewed efficient magma-water interaction and/or collapse of the eruptive column producing pyroclastic density currents and associated co-ignimbritic plumes. The distal tephra deposits might be linked to the widespread lag breccia layer previously identified on the rim of the Mount Rittmann caldera which share the same geochemical composition. Diatoms found in the sediments surrounding the AVT and the primary characteristics of the tephra indicate that the Wood Bay area was open sea at the time of the eruption, which is much earlier than previously thought. AVT is also an excellent tephrostratigraphic marker for the Wood Bay area, in the Ross Sea, and a useful marker for future synchronization of continental ice and marine archives in the region. Highlights: Well-stratified, thick primary tephra found in marine sediments of the Ross Sea, Antarctica. Tephra associated with an eruption of large magnitude and with complex explosive dynamics. Mt. Rittmann is the most probable volcanic source basing on geochemical data. Holocene age determined by 14 C dating of sediments and 40 Ar- 39 Ar dating of the tephra. The tephra represents an excellent tephrostratigraphic marker for the Ross Sea.